Termenul reluării urmăririi penale [Articol] - Bodean, Valeriu (CEP USM, 2020)
The present article contains a brief analysis of the procedural terms in which the criminal prosecution can be resumed after the classification of the criminal trial, the cessation of the criminal prosecution or the removal of the criminal prosecution of the person. Also, the question regarding the term in which the criminal prosecution can be resumed in two other distinct situations, such as: after the suspension of the criminal prosecution and after the acquittal of the person on the ground that the deed was not committed by the defendant, was also addressed. Last but not least, the considerations set out are meant to reveal the connection of the institution to resume criminal prosecution with material law, including in the context of the last legislative changes.
THE TERM OF THE RESUMPTION OF CRIMINAL PROSECUTION
Keywords: urmărire penală; investigație penală